End game strategies towards the total synthesis of vibsanin E, 3-hydroxyvibsanin E, furanovibsanin A, and 3-O-methylfuranovibsanin A - Schwartz, Brett D.; Williams, Craig M.; Bernhardt, Paul V. (Beilstein Journal of Organic Chemistry, 2008)
End game synthetic strategy studies towards the total synthesis of the vibsanin type diterpenes, vibsanin E, 3-hydroxyvibsanin E, furanovibsanin A, and 3-O-methylfuranovibsanin A are discussed, with focus on construction of the side chain and peripheral functionality associated with this group of natural products is the current focus of this report.
Keywords: diterpenes; furanovibsanin A; 3-hydroxyvibsanin E; 3-O-methylfuranovibsanin A; natural products; terpenoids; vibsane; vibsanin E; Viburnum